2020
DOI: 10.5194/acp-20-5977-2020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbonaceous aerosols in Singapore: insight from black carbon fragments and trace metal ions detected by a soot particle aerosol mass spectrometer

Abstract: Abstract. Understanding sources and atmospheric processes that can influence the physiochemical properties of carbonaceous aerosols is essential to evaluate their impacts on air quality and climate. However, resolving the sources, emission characteristics, and aging processes of carbonaceous aerosols in complex urban environments remains challenging. In this work, a soot particle aerosol mass spectrometer (SP-AMS) was deployed to characterize organic aerosols (OAs), refractory black carbon (rBC), and trace met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 85 publications
5
26
0
Order By: Relevance
“…In the previous research, PMF has been used extensively to apportion organics with the standard AMS data but not so often to apportion BC from SP-AMS data Saarikoski et al, 2014). In this research study positive matrix factorisation (PMF) was applied to HR-SP-AMS data to apportion BC in to more than two sources.…”
Section: Positive Matrix Factorisationmentioning
confidence: 99%
“…In the previous research, PMF has been used extensively to apportion organics with the standard AMS data but not so often to apportion BC from SP-AMS data Saarikoski et al, 2014). In this research study positive matrix factorisation (PMF) was applied to HR-SP-AMS data to apportion BC in to more than two sources.…”
Section: Positive Matrix Factorisationmentioning
confidence: 99%
“…The average enhancement factor of f C 2 H 4 O + 2 for alcohol, dicarboxylic acids, and multifunctional groups are 2.62 ± 0.92, 2.90 + 0.78, and 2.69 ± 1.11, respectively. Levoglucosan, a known cellulose-derived compound produced during biomass burning (Simoneit et al, 1999), gives an enhancement of f C 2 H 4 O + 2 by a factor of 2.33. Different to f C 2 H 3 O + /f CO + 2 ratios that show scattered data between vaporization schemes, a strong linear correlation was obtained for all the tested species (R = 0.95) with the slope equal to 2.45.…”
Section: Changes Inmentioning
confidence: 99%
“…In terms of the PMF analysis for the refractory material, rBC and metal fragments are typically included in the mass spectra matrix of organics. For example, Rivellini et al (2020) found five sources for rBC, trace metals and organics in the ambient air of Singapore by applying PMF to the SP-AMS data while Bibi et al (2020) utilized PMF to separate rBC originated from bonfires and domestic wood burning in UK. On the other 60 hand, have investigated the sources of rBC in an underground mine with PMF and Carbone et al (2019) have distinguished fuel and lubricating oil related rBC in the diesel engine exhaust particles in the laboratory by using PMF for the mass spectra of rBC, organics and metals.…”
Section: Introductionmentioning
confidence: 99%
“…One disadvantage of using PMF for the SP-AMS data is that the mass spectra of rBC contains relatively few fragments (typically largest signal observed for C1 + -C5 + fragments), and therefore, the identification of the sources is typically based on organic 65 fragments. However, the rBC mass spectra has been noticed to be somewhat source specific differing for example for laboratory generated rBC particles and particles from aircraft turbine (Corbin et al, 2012), diesel truck and biomass burning particles (Onasch et al, 2015), and ambient hydrocarbon like organic aerosol (HOA) and oxygenated organic aerosol (OOA) factors (Rivellini et al, 2020). One option to improve the separation of BC sources is to include larger Cx fragments in the PMF matrix, as was done in the study of Bibi et al (2020), where 70 the addition of fullerenes signals (for example C60 + ) increased the number of meaningful sources.…”
Section: Introductionmentioning
confidence: 99%